2‐Aminothiophene derivatives as a new class of positive allosteric modulators of glucagon‐like peptide 1 receptor. (4th April 2022) - Redij, Tejashree; McKee, James A.; Do, Phu; Campbell, Jeffrey A.; Ma, Jian; Li, Zhiyu; Miller, Nicholas; Srikanlaya, Chananchida; Zhang, Dianzheng; Hua, Xianxin; Li, Zhijun
Abstract: We report the discovery of two new 2‐aminothiophene based small molecule positive allosteric modulators (PAMs) of glucagon‐like peptide 1 receptor (GLP‐1R) for the treatment of type 2 diabetes. One of the chemotypes, (S‐1 ), has a molecular weight of 239 g/mol, the smallest molecule among all reported GLP‐1R PAMs. When combined with GLP‐1 peptide, S‐1 increased the GLP‐1R activity in a dose‐dependent manner in a cell‐based assay. When combined with the peptide agonist of vasoactive intestinal polypeptide receptor 1 (VIPR1), S‐1 showed no specific activity on VIPR1, another class B GPCR present in the same HEK293‐CREB cell line. Insulin secretion studies found S‐1 combined with GLP‐1 increased insulin secretion by 1.5‐fold at 5 μM. In a mechanistic study, evidence is provided that the synergistic effect of S‐1 with GLP‐1 may be partly due to the enhanced impact on CREB based phosphorylation. Given the favorable profile of these chemotypes, the work reported herein suggests that 2‐aminothiophene derivatives are a new and promising class of GLP‐1R PAMs. Abstract : 2‐Aminothiophene (2‐AT) derivatives represent a new and promising class of GLP‐1R‐positive allosteric modulators. 2‐AT derivatives are easy to synthesize and have favorable pharmacological properties.